UV-curable multicolor coating composition and preparation method thereof

By using water-based UV resin and partially hydrophobic nano-scale inorganic oxides in water-based colorful coatings, combining photoinitiators and colored glue particles, UV curing colorful coating composition is solved, and the problem of slow curing rate of water-based colorful coatings is achieved. High stability and performance, and rapid curing process.

CN119463660APending Publication Date: 2025-02-18SKSHU PAINT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411456939.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When used outdoors, the water-based colorful paint has a slow curing rate and cannot even cure due to weather conditions, which affects the coating performance.

Method used

A water-based UV resin is used as the main film-forming resin, and some hydrophobic nano-scale inorganic oxides are added, combined with a photoinitiator and a colored rubber particle dispersion to form a UV cured colorful coating composition.

Benefits of technology

Improves the stability and coating properties of the coating composition, such as adhesion and hardness, faster curing speed, and initial curing can be achieved in just a few minutes of sunlight exposure, significantly saving construction time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a UV-curable multicolor coating composition and a preparation method thereof, and relates to the technical field of water-based UV coatings. The UV-cured multicolor coating composition comprises the following raw material components in parts by weight: 100 parts of a first water-based UV resin dispersion liquid, 0.5-10 parts of a partially hydrophobic nanoscale inorganic oxide, 0.5-2 parts of a photoinitiator and 100-300 parts of a colorful colloidal particle dispersion liquid. Preferably, the methanol value of the partially hydrophobic nanoscale inorganic oxide is 10 to 50. Part of the hydrophobic nanoscale inorganic oxide is added into the UV curing colorful coating composition, so that the dispersion stability of the colorful colloidal particle dispersion liquid is improved, and the performance of a coating after the coating is cured is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water-based UV coatings and relates to a UV-curable multi-color coating composition and a preparation method thereof. Background Art

[0002] Water-based multi-color paint is currently the mainstream choice for imitation stone paint. Due to the characteristics of water-based multi-color paint, the current water-based multi-color paint is generally composed of base paint, protective glue and continuous phase, and forms a film through natural drying. Since water-based multi-color paint is mainly used outdoors, the outdoor weather greatly affects the curing rate and coating performance of water-based multi-color paint. For example, high humidity and low temperature in the air will affect the curing rate of water-based multi-color paint, or even make it impossible to cure.

[0003] UV coatings have the characteristics of fast curing speed, and the coating can be cured in a few minutes under direct sunlight, which is more conducive to construction. However, there are no reports on water-based multi-color coatings based on UV curing. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a UV curable multi-color coating composition and a preparation method thereof.

[0005] The technical solution of the present invention is as follows:

[0006] A UV curable multi-color coating composition comprises raw material components by weight: 100 parts of a first aqueous UV resin dispersion, 0.5-10 parts of partially hydrophobic nano-scale inorganic oxides, 0.5-2 parts of a photoinitiator and 100-300 parts of a color colloidal particle dispersion.

[0007] Preferably, the first aqueous UV resin dispersion is selected from one or a combination of two or more of aqueous UV polyurethane emulsion, acrylate-modified aqueous UV polyurethane emulsion and silicone-modified aqueous UV polyurethane emulsion.

[0008] Preferably, the surface of the partially hydrophobic nanoscale inorganic oxide is grafted with carbon-carbon unsaturated double bonds;

[0009] The methanol value of the partially hydrophobic nano-scale inorganic oxide is 10-50.

[0010] More preferably, the partially hydrophobic nanoscale inorganic oxide is obtained by reacting a hydrophilic nanoscale inorganic oxide with a silane coupling agent containing a carbon-carbon double bond.

[0011] Further preferably, the hydrophilic nanoscale inorganic oxide is selected from one or a combination of two or more of nano-silicon dioxide, nano-titanium dioxide, nano-aluminum oxide, nano-zinc oxide, nano-zirconium dioxide and nano-cerium dioxide.

[0012] Further preferably, the structure of the carbon-carbon double bond-containing silane coupling agent is as shown in the following formula (1):

[0013] CH 2 =C(R 1 )R 2 S i 3 x (OR 4 ) 3-x (1)

[0014] Among them, R 1 is selected from H or C1-C4 alkyl, R 2 is absent, C1-C6 alkylene or C2-C8 substituted alkylene, R 3 and R 4 Independently selected from C1-C4 alkyl, x=0-1.

[0015] Preferably, the colored colloidal particle solution is composed of UV base paint and protective colloid in a ratio of 1:0.5-1.6;

[0016] The UV base paint is composed of 100% by weight: 10-20% of the second aqueous UV resin dispersion, 0.5-2% of the first dispersant, 0.3-1% of the first wetting agent, 0.1-0.6% of the first preservative, 10-40% of the filler, 0.1-1% of the first thickener, 0.2-1% of the first defoamer, 0.1-1.5% of the first thixotropic agent, 3-10% of the first film-forming aid, 1-5% of the first antifreeze agent, and the balance is water;

[0017] The protective colloid is composed of 5-10% protective colloid powder and the balance water according to 100% by weight.

[0018] More preferably, the aqueous UV polyurethane emulsion, acrylate-modified aqueous UV polyurethane emulsion and silicone-modified aqueous UV polyurethane emulsion are selected from one or a combination of two or more thereof.

[0019] Preferably, the raw material components further include one or a combination of two or more of an anti-yellowing agent, a second film-forming aid, a second dispersant, a second wetting agent, a second thickener, a second thixotropic agent and a second antifreeze agent.

[0020] The method for preparing the UV-curable multi-color coating composition described in any of the above embodiments comprises mixing and evenly dispersing the raw material components to obtain the UV-curable multi-color coating composition.

[0021] The beneficial effects of the present invention are as follows: the present invention adopts water-based UV resin as the main film-forming resin and adds some hydrophobic nano-scale inorganic oxides, which not only improves the stability of the coating composition, but also improves the performance of the coating, such as better adhesion, higher hardness, and fast curing. Only a few minutes of sunlight exposure is required for the next step of construction, which can greatly save construction time. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further illustrated and described below through specific implementation methods.

[0023] In order to improve the curing rate and performance of water-based multi-color coatings, the present invention provides a UV-curable multi-color coating composition, the raw material components comprising, by weight, 100 parts of a first water-based UV resin dispersion, 0.5-10 parts of partially hydrophobic nano-scale inorganic oxides, 0.5-2 parts of a photoinitiator and 100-300 parts of a color colloidal particle dispersion.

[0024] The present invention adopts the first water-based UV resin dispersion as the main resin, and the UV resin cures very quickly under sunlight (ultraviolet rays), and preliminary curing can be achieved in a few minutes, thereby improving the workability of the water-based multi-color coating, and the next process can be carried out very quickly, while the multi-color coating in the prior art generally needs to be coated with multiple layers, and the next layer can be implemented only after the previous layer is actually dried, which takes a long time, generally requiring 12-24 hours. Partial hydrophobic nano-scale inorganic oxides are added to the UV-curable multi-color coating composition of the present invention, which can improve the performance of the coating, such as hardness, adhesion strength, etc., and also contribute to the stability of the colored colloidal particle dispersion in the multi-color coating composition. In the present invention, further, the number of parts of the partial hydrophobic nano-scale inorganic oxides is 2-10 parts, and for example, it can be any value or any value between 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc., without special restrictions. In the present invention, the amount of the colored colloidal particle dispersion can be any value among 100 parts, 150 parts, 200 parts, 250 parts, 300 parts, etc. or any value in between, without any particular limitation.

[0025] In a preferred embodiment of the present invention, the first aqueous UV resin dispersion is selected from one or a combination of two or more of aqueous UV polyurethane emulsion, acrylate-modified aqueous UV polyurethane emulsion and silicone-modified aqueous UV polyurethane emulsion. Aqueous UV polyurethane emulsion, acrylate-modified aqueous UV polyurethane emulsion and silicone-modified aqueous UV polyurethane emulsion can be prepared according to the prior art or directly obtained from the market, such as UV215, UV210, UV206, etc. of Guangdong Xidun New Material Technology Co., Ltd.

[0026] In a preferred embodiment of the present invention, a portion of the hydrophobic nanoscale inorganic oxide surface is grafted with carbon-carbon unsaturated double bonds;

[0027] The methanol value of some hydrophobic nano-sized inorganic oxides is 10-50.

[0028] The surface grafting of nano-scale inorganic oxides with carbon-carbon unsaturated double bonds can not only improve the hydrophobicity of the nano-scale inorganic oxides, but also introduce carbon-carbon double bonds, which can participate in the curing of UV resins. In addition, the nano-scale inorganic oxides are partially hydrophobic and not so hydrophobic, so they can be dispersed into the coating composition with the help of additives such as dispersants in the coating composition, and the nano-scale inorganic oxides can be dispersed into the cured resin through chemical bonding, which can further improve the performance of the coating.

[0029] The methanol value can reflect the hydrophobicity of nano-scale inorganic oxides. The higher the methanol value, the stronger the hydrophobicity, and vice versa. Under normal circumstances, hydrophilic nano-inorganic oxides can be dispersed in water. As the hydrophobicity of nano-inorganic oxides increases, their dispersibility in water also decreases. The dispersibility can be improved by adding methanol. The test method of methanol value is generally as follows: add 0.2g of the nano-scale inorganic oxide to be tested into 50ml of water and turn on magnetic stirring. The hydrophobic nano-scale inorganic oxide floats on the water surface. Methanol is gradually dripped in. When the methanol dripped in just allows the nano-scale inorganic oxide to be evenly dispersed in the solution, the amount of methanol added at this time is xml, and the methanol value is: x / (x+50)×100%. The methanol value of a completely hydrophobic nano-scale inorganic oxide is generally not less than 60.

[0032] Further preferably, the methanol value of the partially hydrophobic nanoscale inorganic oxide is 10-30. For example, the methanol value can be any value among 10, 12, 15, 16, 18, 20, 22, 24, 25, 27, 28, 30, etc. or any value in between, without particular limitation.

[0033] In a more preferred embodiment of the present invention, the partially hydrophobic nanoscale inorganic oxide is obtained by reacting a hydrophilic nanoscale inorganic oxide with a carbon-carbon double bond-containing silane coupling agent. The partially hydrophobic nanoscale inorganic oxide is prepared by reacting a carbon-carbon double bond-containing silane coupling agent with a hydrophilic nanoscale inorganic oxide, which has the characteristics of efficient and controllable reaction, and the post-treatment is relatively simple.

[0034] In a further preferred embodiment of the present invention, the average particle size of the hydrophilic nano-scale inorganic oxide can be 1-100 nm, and can be selected from one or a combination of two or more of nano-silicon dioxide, nano-titanium dioxide, nano-aluminum oxide, nano-zirconia, nano-cerium dioxide. The most commonly used hydrophilic nano-scale inorganic oxide is nano-silicon dioxide.

[0035] In a further preferred embodiment of the present invention, the structure of the silane coupling agent containing a carbon-carbon double bond is as shown in the following formula (1):

[0036] CH 2 =C(R 1 )R 2 S i 3 x (OR 4 ) 3-x (1)

[0037] Among them, R 1 is selected from H or C1-C4 alkyl, R 2 is absent, C1-C6 alkylene or C2-C8 substituted alkylene, R 3 and R 4 Independently selected from C1-C4 alkyl, x=0-1.

[0038] The alkoxy group in the silane coupling agent has high reactivity, and the surface of the hydrophilic nano-scale inorganic oxide has abundant silanol groups. The alkoxy group in the silane coupling agent has high reactivity, and can react with the silanol groups and remove small molecule alcohols, and the carbon-carbon double bond structure is grafted on the surface of the inorganic oxide. For example, the carbon-carbon double bond-containing silane coupling agent can be vinyl trimethoxysilane, vinyl triethoxysilane, vinyl methyl dimethoxysilane, vinyl methyl diethoxysilane, methacryloxypropyl trimethoxysilane, methacryloxypropyl triethoxysilane, methacryloxypropyl methyl dimethoxysilane, etc., which can be directly purchased from the market.

[0039] In a preferred embodiment of the present invention, the colored colloidal particle solution is composed of UV base paint and protective colloid in a ratio of 1:0.5-1.6;

[0040] The UV base paint is composed of 100% by weight: 10-20% of the second aqueous UV resin dispersion, 1-2% of the first dispersant, 0.5-1% of the first wetting agent, 0.1-0.6% of the first preservative, 10-40% of the filler, 0.1-1% of the first thickener, 0.2-1% of the first defoamer, 0.1-1.5% of the first thixotropic agent, 3-10% of the first film-forming aid, 1-5% of the first antifreeze agent, and the balance is water;

[0041] The protective colloid is composed of 5-10% protective colloid powder and the balance water according to 100% by weight.

[0042] In the present invention, the base paint adopts the second water-based UV resin dispersion, which also has good sunlight curing performance, and is conducive to the rapid curing of the colorful paint under sunlight. The protective rubber powder is selected from lithium magnesium silicate or aluminum magnesium silicate.

[0043] In a more preferred embodiment of the present invention, the second aqueous UV resin dispersion is selected from one or a combination of two or more of aqueous UV polyurethane emulsion, acrylate-modified aqueous UV polyurethane emulsion and silicone-modified aqueous UV polyurethane emulsion.

[0044] In a preferred embodiment of the present invention, the raw material components further include one or a combination of two or more of an anti-yellowing agent, a second film-forming aid, a second dispersant, a second wetting agent, a second thickener, a second thixotropic agent and a second antifreeze agent.

[0045] In the present invention, the first wetting agent and the second wetting agent can both be polyether modified silicone oil; the first thickener and the second thickener can both be hydrophobically associating polyurethane thickeners, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, etc.; the first thixotropic agent and the second thixotropic agent can both be fumed silica, organic bentonite, etc.; the first antifreeze agent and the second antifreeze agent can both be ethylene glycol, propylene glycol, etc.; the first film-forming aid and the second film-forming aid can both be propylene glycol ethyl ether, propylene glycol butyl ether, lauryl alcohol ester, etc.; various additives in the present invention can be directly purchased from the market.

[0046] The present invention also provides a method for preparing the UV curable multi-color coating composition described in any one of the above embodiments, wherein the raw material components are mixed and dispersed uniformly to obtain the UV curable multi-color coating composition.

[0047] The technical solution of the present invention is further described and illustrated according to various embodiments below. Unless otherwise specified, the parts described in the following embodiments are parts by weight.

[0048] Preparation Example 1-3 Preparation of partially hydrophobic nano inorganic oxides

[0049] Preparation Example 1

[0050] 5 parts of hydrophilic silica with an average particle size of 20 nm were added to 100 parts of anhydrous ethanol and ultrasonically dispersed for 10 minutes, 0.05 parts of vinyl triethoxysilane were added, and stirred at room temperature for 4 hours. The solid was separated and dried in an oven at 60°C overnight to obtain modified nano-silica. The methanol value of the modified nano-silica was measured to be 15.

[0051] Preparation Example 2

[0052] The difference between this preparation example and preparation example 1 is that in preparation example 1, the amount of vinyl triethoxysilane is adjusted from 0.2 parts to 0.15 parts, and the mixture is stirred at room temperature for 3 hours. The remaining steps remain unchanged. The methanol value of the modified nano-silica obtained in this preparation example is measured to be 30.

[0053] Preparation Example 3

[0054] The difference between this preparation example and preparation example 1 is that in preparation example 1, the amount of vinyl triethoxysilane is adjusted from 0.2 parts to 0.3 parts, and the mixture is stirred at room temperature for 2 hours. The remaining steps remain unchanged. The methanol value of the modified nano-silica obtained in this preparation example is measured to be 45.

[0055] Comparative Preparation Example 1

[0056] The difference between this comparative preparation example and preparation example 1 is that in preparation example 1, the amount of vinyl triethoxysilane is adjusted from 0.2 parts to 1 part. The remaining steps remain unchanged. The methanol value of the modified nano-silica obtained in this preparation example is measured to be 70.

[0057] Example 1

[0058] UV base paint, based on 100% by weight, is composed of: 15% water-based UV resin emulsion UV215, 1.1% BYK-155, 0.6% Tego 4100, 0.2% preservative, 15% titanium dioxide, 20% kaolin, 0.2% water-based polyurethane associative thickener, 0.2 hydroxyethyl cellulose, 0.6% dimethyl silicone defoamer, 0.6% organic bentonite, 5% propylene glycol butyl ether, 2% ethylene glycol, and the balance is water;

[0059] Add UV215 to the container, then add BYK-155, Tego 4100, and dimethyl silicone defoamer, stir and disperse at 800 rpm for 15 minutes, then add titanium dioxide and kaolin, stir and disperse at 1500 rpm for 25 minutes, then add the remaining raw material components, stir and disperse at 600 rpm for 30 minutes to obtain UV base paint.

[0060] The protective colloid is composed of 7% lithium magnesium silicate and the balance water according to 100% by weight. Lithium magnesium silicate is directly added to water and stirred and dispersed at a stirring speed of 900 rpm until it becomes a uniform state to obtain a protective colloid.

[0061] The UV curable multi-color coating composition comprises, by weight, 100 parts of aqueous UV resin emulsion UV215, 5 parts of modified nano-silica of Preparation Example 1, 1.1 parts of aqueous photoinitiator 500 and 150 parts of color colloidal particle dispersion, 0.5% BYK-155, 0.4% Tego 4100, 0.1% preservative, 0.5% aqueous polyurethane associative thickener, 0.3% dimethyl silicone defoamer, 0.5% organic bentonite, 3% propylene glycol butyl ether, and 2% ethylene glycol.

[0062] UV215 and modified nano-silica were added to a container, stirred and dispersed at a stirring speed of 1500 rpm for 20 minutes, and then the remaining raw material components were added, stirred and dispersed at a stirring speed of 800 rpm for 30 minutes to obtain a UV-curable multi-color coating composition.

[0063] The color colloidal particle dispersion is composed of the above UV base paint and protective colloid in a weight ratio of 1:0.8.

[0064] Example 2

[0065] The difference between this example and Example 1 is that in Example 1, the modified silicon dioxide in Preparation Example 1 is replaced by an equal weight of modified silicon dioxide in Preparation Example 2. The remaining steps remain unchanged.

[0066] Example 3

[0067] The difference between this example and Example 1 is that in Example 1, the modified silicon dioxide in Preparation Example 1 is replaced by an equal weight of modified silicon dioxide in Preparation Example 3. The remaining steps remain unchanged.

[0068] Comparative Example 1

[0069] The difference between this comparative example and Example 1 is that in Example 1, the modified silicon dioxide in Preparation Example 1 is replaced by an equal weight of the modified silicon dioxide in Comparative Preparation Example 1. The remaining steps remain unchanged.

[0070] Comparative Example 2

[0071] The difference between this comparative example and Example 1 is that in Example 1, the modified silica in Preparation Example 1 is replaced by an equal weight of the hydrophilic silica in Preparation Example 1. The remaining steps remain unchanged.

[0072] Example 4

[0073] UV base paint, based on 100% by weight, is composed of: 18% water-based UV resin emulsion UV215, 0.8% BYK-155, 0.5% Tego 4100, 0.2% preservative, 20% titanium dioxide, 10% kaolin, 0.2% water-based polyurethane associative thickener, 0.3 hydroxyethyl cellulose, 0.7% dimethyl silicone defoamer, 0.8% organic bentonite, 5% propylene glycol butyl ether, 2.5% ethylene glycol, and the balance is water;

[0074] The protective colloid is composed of 10% by weight of lithium magnesium silicate and the balance of water.

[0075] The UV curable multi-color coating composition comprises, by weight, 100 parts of aqueous UV resin emulsion UV215, 0.5 parts of modified nano-silica of Preparation Example 2, 1.3 parts of aqueous photoinitiator 500 and 200 parts of color colloidal particle dispersion, 0.7% BYK-155, 0.5% Tego 4100, 0.1% preservative, 0.4% aqueous polyurethane associative thickener, 0.3% dimethyl silicone defoamer, 0.5% organic bentonite, 4% propylene glycol butyl ether, and 2% ethylene glycol.

[0076] The color colloidal particle dispersion is composed of the above UV base paint and protective colloid in a weight ratio of 1:1.2.

[0077] Example 5

[0078] The difference between this example and Example 4 is that in Example 4, the modified silicon dioxide in Preparation Example 2 is adjusted from 0.5 parts to 2 parts. The other steps remain unchanged.

[0079] Example 6

[0080] The difference between this example and Example 4 is that in Example 4, the modified silicon dioxide in Preparation Example 2 is adjusted from 0.5 parts to 6 parts. The other steps remain unchanged.

[0081] Example 7

[0082] The difference between this example and Example 4 is that in Example 4, the modified silicon dioxide in Preparation Example 2 is adjusted from 0.5 parts to 10 parts. The other steps remain unchanged.

[0083] Comparative Example 3

[0084] The difference between this comparative example and Example 4 is that in Example 4, the modified silicon dioxide in Preparation Example 2 is adjusted from 0.5 parts to 0 parts. The other steps remain unchanged.

[0085] Performance Testing

[0086] Storage stability: Hot and cold storage tests are conducted at 50°C and -5°C for 7 days respectively to observe whether there are any abnormalities such as stratification, precipitation, degeneration, particle coarsening, and agglomeration.

[0087] The curing conditions of the coating composition to be tested are: the coating composition spraying thickness is 0.2 mm, the light intensity is 1.5 mW / mm 2 The surface was initially cured by irradiating with artificial sunlight for 5 minutes, then spraying the second coat with a thickness of 0.2 mm, and continuing to irradiate under the above artificial sunlight for 5 minutes, spraying the third coat with a thickness of 0.3 mm, and continuing to irradiate under the above artificial sunlight for 5 minutes, and then drying at room temperature for 24 hours.

[0088] Water resistance and alkali resistance: Performance test is carried out in accordance with HG / T4343-2012 "Water-based multi-color architectural coatings".

[0089] Adhesion: Measured according to the method of GB / T9286-2021 "Scratching test for paint and varnish films". Grade 0 is the best and grade 5 is the worst.

[0090] Pencil hardness: GB / T 6739-2006 "Paints and varnishes - Determination of film hardness by pencil method".

[0091] The results are shown in Table 1 below.

[0092] Table 1

[0093]

[0094] As can be seen from the results of the above performance tests, the UV curing multi-color coating of the present invention can continue to apply the next one after 5 minutes of sunlight exposure between each process, while the conventional multi-color coating generally takes 2 hours to dry, and it takes about 12-24 hours to reach the actual drying and proceed to the next process. Therefore, the UV curing multi-color coating of the present invention can greatly save construction time. In addition, the addition of partially hydrophobic nano-silicon dioxide can significantly improve the stability of the coating, and also has a greater improvement effect on adhesion and hardness.

[0095] As described above, the basic principles, main features and advantages of the present invention are shown and described. Those skilled in the art should understand that the present invention is not limited by the above embodiments, which are only preferred embodiments of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the scope of the present invention and the content of the specification should still be within the scope of the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents.

Claims

1. A UV curable multi-color coating composition, characterized in that: The raw material components include, by weight, 100 parts of a first aqueous UV resin dispersion, 0.5-10 parts of partially hydrophobic nano-scale inorganic oxides, 0.5-2 parts of a photoinitiator and 100-300 parts of a color colloidal particle dispersion.

2. The UV curable multi-color coating composition according to claim 1, characterized in that: The first aqueous UV resin dispersion is selected from one or a combination of two or more of aqueous UV polyurethane emulsion, acrylate-modified aqueous UV polyurethane emulsion and silicone-modified aqueous UV polyurethane emulsion.

3. The UV curable multi-color coating composition according to claim 1, characterized in that: The surface of the partially hydrophobic nanoscale inorganic oxide is grafted with carbon-carbon unsaturated double bonds; The methanol value of the partially hydrophobic nano-scale inorganic oxide is 10-50.

4. The UV curable multi-color coating composition according to claim 3, characterized in that: The partially hydrophobic nanometer-scale inorganic oxide is obtained by reacting a hydrophilic nanometer-scale inorganic oxide with a carbon-carbon double bond-containing silane coupling agent.

5. The UV curable multi-color coating composition according to claim 4, characterized in that: The hydrophilic nano-scale inorganic oxide is selected from one or a combination of two or more of nano-silicon dioxide, nano-titanium dioxide, nano-aluminum oxide, nano-zinc oxide, nano-zirconium dioxide and nano-cerium dioxide.

6. The UV curable multi-color coating composition according to claim 4, characterized in that: The structure of the carbon-carbon double bond-containing silane coupling agent is shown in the following formula (1): CH2=C(R 1 )R 2 SiR 3 x (OR 4 ) 3-x (1) Among them, R 1 is selected from H or C1-C4 alkyl, R 2 is absent, C1-C6 alkylene or C2-C8 substituted alkylene, R 3 and R 4 Independently selected from C1-C4 alkyl, x=0-1.

7. The UV curable multi-color coating composition according to claim 1, characterized in that: The colored colloidal particle solution is composed of UV base paint and protective colloid in a ratio of 1:0.5-1.6; The UV base paint is composed of 100% by weight: 10-20% of the second aqueous UV resin dispersion, 0.5-2% of the first dispersant, 0.3-1% of the first wetting agent, 0.1-0.6% of the first preservative, 10-40% of the filler, 0.1-1% of the first thickener, 0.2-1% of the first defoamer, 0.1-1.5% of the first thixotropic agent, 3-10% of the first film-forming aid, 1-5% of the first antifreeze agent, and the balance is water; The protective colloid is composed of 5-10% protective colloid powder and the balance water according to 100% by weight.

8. The UV curable multi-color coating composition according to claim 7, characterized in that: The second aqueous UV resin dispersion is selected from one or a combination of two or more of aqueous UV polyurethane emulsion, acrylate-modified aqueous UV polyurethane emulsion and silicone-modified aqueous UV polyurethane emulsion.

9. The UV curable multi-color coating composition according to claim 1, characterized in that: The raw material components further include one or a combination of two or more of an anti-yellowing agent, a second film-forming aid, a second dispersant, a second wetting agent, a second thickener, a second thixotropic agent and a second antifreeze agent.

10. The method for preparing a UV curable multi-color coating composition according to any one of claims 1 to 9, characterized in that: The raw material components are mixed and dispersed uniformly to obtain the product.